Handling E-Waste in Malaysia: Management,Policies and Strategies - Nurul Aini, Osman; Norazli, O.; Roslina, M.; Shreeshivadasan, C. (2016)
One of the concerns of life is the generation of waste. In today’s modern life, the generation of the new type of waste is the waste of electrical and electronic equipment’s or e-waste becoming a crucial problems to solve. E-waste containing both dangerous and valuable materials requiring a special treatment and recycling practices to avoid adverse environmental impacts and harmful impact on human health. Domestic ewaste generation in Malaysia has already climbed dramatically and forecasted to reach over a million tons in 2020. This increasing trend amount of e-waste is due to the high demand on the production of electric and electrical equipment from the Malaysia’s consumers. Various steps been taken by government in order to tackle the ever growing threat of e-waste. This paper presents global and Malaysia e-waste scenario, initiatives and practices in handling an e-waste. Consequently, this paper suggest that e-waste policy development is crucial in Malaysia and requires more customized approach and a strategies environment assessment as part of national policy planning.